Finding the right title for your article: Advice for academic authors - van Teijlingen, E; Ireland, J; Hundley, V; Simkhada, P; Sathian, Brijesh (Nepal Journal of Epidemiology, 2014)
On reading the title of an article the reader can sometimes wonder what the author is trying to say, as the title seems so far removed from the research covered in the article. Do such authors forget that many readers of health and medical journals browse the list of contents (in a paper or electronic format) and use titles to select the article that attracts attention? Academic authors are often not clear enough in the titles of their articles, and hence may not attract as large a readership as possible. Any author would want their article to be read and cited, and to stand out in a crowded Table of Contents or a list of papers found in a search on electronic databases. DOI: http://dx.doi.org/10.3126/nje.v4i1.10138 Nepal Journal of Epidemiology 2014;4 (1): 344-347